Extract of Marsdenia tenacissima (Roxb.) Moon [Apocynaceae] Suppresses Hepatocellular Carcinoma by Inhibiting Angiogenesis - Pan, Yating; Liao, Xinyi; Yang, Lili; Zhang, Chunlei; Wang, Jue; Zheng, Peiyong; Yu, Guanzhen; Song, Haiyan (Frontiers in Pharmacology, 2022)
The extract of Marsdenia tenacissima (Roxb.) Moon [Apocynaceae] (MTE) has shown a significant anti-cancer effect on hepatocellular carcinoma (HCC), but its mechanism remains unclear. In this study, we used transcriptomics methods to investigate the underlying mechanism of MTE against HCC. Both MHCC97H and HepG2 cell lines were treated with MTE. The cell viability and migration were measured using the Cell Counting Kit-8 assay and Transwell assay. RNA-sequence was used to identify differentially expressed genes (DEGs) between HepG2 cells treated with and without MTE. The expression levels of selected DEGs—vascular endothelial growth factor-A (VEGFA), platelet derived growth factor receptor-β (PDGFRB) and von willebrand factor (VWF) were verified by RT-PCR and Western blot. The effect of conditioned medium from HCC cells with MTE treatment (CM-MTE) on blood vessels was observed by tube formation assay of HUVECs and chick chorioallantoic membrane (CAM) assay. A mouse model of HCC patient-derived tumor xenograft (PDX) was established and treated with MTE. The effect of MTE on the growth and angiogenesis of HCC-PDX was analyzed. The results demonstrated that MTE inhibited the viability and migration of HCC cells. RNA-seq showed that MTE treatment downregulated of multiple genes associated with metabolism and angiogenesis. Expression levels of VEGFA, VWF, and PDGFRB in HCC cells were significantly suppressed by MTE. Meanwhile, MTE effectively inhibited the tube-forming capability of HUVECs and the angiogenesis of chick CAM. In vivo experiments revealed that the extract reduced tumor volume, inhibited the proliferation of HCC cells, and expanded the necrotic area of the tumor. Immunohistochemical results showed that the expression levels of CD31, PDGFB, VEGF, VWF, and PDGFRB in the HCC-PDX tumor tissues were all downregulated by MTE in a dose-dependent manner. Taken together, MTE could inhibit angiogenesis through repressing the expression of VEGF, VWF, and PDGFRB in HCC cells, a mechanism that may enable MTE to counter HCC development.